2023
DOI: 10.3389/fonc.2023.1104242
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of doublet and triplet therapies for metastatic hormone-sensitive prostate cancer: A systematic review and network meta-analysis

Abstract: BackgroundThe best choice of first-line treatment for metastatic hormone-sensitive prostate cancer (mHSPC) is unclear. We aimed to compare the effectiveness and safety determined in randomized clinical trials of doublet and triplet treatments for mHSPC.MethodsMedline, Embase, Cochrane Central and ClinicalTrials.gov were searched from inception through July 01, 2022. Eligible studies were phase III randomized clinical trials evaluating androgen deprivation treatment (ADT) alone, doublet therapies [ADT combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…11 Several clinical factors should be considered including burden of disease, visceral metastases (especially liver), performance status, and synchronous versus metachronous at presentation. [12][13][14] A majority of prostate cancer patients in Canada die having never received docetaxel despite its survival benefits, reflecting challenges of applying trial data to real world patients who are older with more comorbidities. A Canadian retrospective population-based study showed that only 11% of de novo mCSPC patients received ADT-docetaxel when it was the only available ADT-intensification option and only 44% completed ≥6 cycles of docetaxel.…”
Section: Discussionmentioning
confidence: 99%
“…11 Several clinical factors should be considered including burden of disease, visceral metastases (especially liver), performance status, and synchronous versus metachronous at presentation. [12][13][14] A majority of prostate cancer patients in Canada die having never received docetaxel despite its survival benefits, reflecting challenges of applying trial data to real world patients who are older with more comorbidities. A Canadian retrospective population-based study showed that only 11% of de novo mCSPC patients received ADT-docetaxel when it was the only available ADT-intensification option and only 44% completed ≥6 cycles of docetaxel.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in OS with ADT plus ARPI plus docetaxel vs ADT plus docetaxel have been confirmed in several meta-analyses, with indirect network meta-analyses suggesting that the triple regimen may also rank ahead of ADT plus ARPI . The efficacy benefit of ADT plus ARPI plus docetaxel over ADT plus ARPI needs to be confirmed in prospective head-to-head studies.…”
Section: Observationsmentioning
confidence: 99%
“…The usage of ARTA is recommended in combination with androgen deprivation therapy (ADT) or in triplet combination with ADT and chemotherapy in mPCa. Although the triplet combination has shown superior efficacy compared to the doublet combination in high-volume prostate cancer, it is important to note that the incidence of adverse events is also higher [20]. The potential relationship between the molecular pathways of metformin and silodosin in the treatment of prostate cancer suggests that both drugs should be considered as viable adjunctive therapies in the management of mPCa.…”
Section: Introductionmentioning
confidence: 99%